Household Food Insecurity among Indigenous Communities in Sarawak, Malaysia : Predictors and Coping Strategies - Teoh, Wan Jool; Law, Leh Shii; Helmy, Hazmi; Jeffery, Stephen; Cheah, Whye Lian; Yolanda, Salleh (Wolters Kluwer - Medknow, 2024)
Background: Food insecurity prevails in people at all phases of their life course and causes remarkable health, social, and financial repercussions. In Sarawak state, Malaysia, information regarding household food insecurity is limited.